The optimal neoadjuvant treatment strategy for HR+/HER2 + breast cancer: a network meta-analysis - Shiwei Liu; Miao Yu; Exian Mou; Meihua Wang; Shuanghua Liu; Li Xia; Hui Li; Hao Tang; Yajing Feng; Xin Yu; Kun Mi; Hao Wang (Scientific Reports)
Abstract The efficacy of neoadjuvant therapy varies significantly with hormone receptor (HR) status for patients with human epidermal growth factor receptor 2 (HER2) positive breast cancer (BC). Despite extensive research on HER2 + BC, the optimal neoadjuvant strategy for HR+/HER2 + BC remains inconclusive. This study aimed to identify the optimal neoadjuvant regimen for HR+/HER2 + BC treatment. We conducted a systematic search for trials comparing neoadjuvant regimens for HR+/HER2 + BC and a network meta-analysis. Odds ratios for pathological complete response (pCR) and hazard ratios for event-free survival (EFS) were calculated. Treatment regimens were ranked using the surface under the cumulative ranking curve. 20 trials with 2809 patients were included. In pCR analysis, three neoadjuvant regimens sequentially ranked at the top, namely those comprising T-DM1, pertuzumab with trastuzumab, and tyrosine kinase inhibitor with trastuzumab, demonstrating significantly higher pCR rates than monotherapies. In EFS analysis, pertuzumab with trastuzumab ranked the first while T-DM1 containing regimen ranked the last. Anthracycline-free regimens showed a marginally higher pCR rate than anthracycline-containing regimens, while carboplatin-containing regimens demonstrated a numerically higher pCR rate than carboplatin-free regimens. Significant heterogeneity was observed in endocrine therapy analysis, which may be caused by different strategies for incorporating endocrine therapy. In conclusion, trastuzumab plus pertuzumab stands out as the optimal neoadjuvant HER2-targeting regimen for HR+/HER2 + BC Furthermore, anthracycline-free carboplatin-containing chemotherapy emerges as a promising combination treatment. Further investigation is required to clarify the role of endocrine therapy in HR+/HER2 + BC to guide its clinical application.